Soil fertility of two hundred properties in the southwest Paraná with the presence of native fruit trees - Cassol, Darcieli Aparecida; Wagner Júnior, Américo; Donazzolo, Joel; Cassol, Luis César; das Dores Abati Miranda, Fabiani; Conceição, Paulo Cesar (Scientia Agraria Paranaensis, 2021)
The native fruit trees are of great importance to the Southwest Region of Paraná biome, but little is known about them, especially as the soil fertility in which they are found. Such information is necessary when domestication is intended for orchards usage. The objective of this work was to collect information on the distribution of the native fruit trees in relation to the chemical characteristics of the soil in which they are found, in four municipalities of the Phytophysiognomy Forest and Araucária (DoisVizinhos, Itapejara do Oeste, Verê and São Jorge d'Oeste). The chemical soil characterization for the native fruit trees were applied in the species of jaboticaba tree (Plinia sp.), Surinam cherry tree (Eugenia uniflora L.), sete-capote tree [Campomanesia guazumifolia (Cambess.) O. Berg], cereja-do-mato tree (Eugenia involucrata DC.), guabiroba tree (Campomanesia xanthocarpa Berg), guabiju tree (Myrcianthes pungens), feijoa tree [Acca selowiana (O. Berg) Burret], uvaia tree (E. pyriformis Cambess), yellow and red araça trees (Psidium cattleyanum Sabine). The soil was collected in two hundred properties with the presence of at least some native fruit of natural occurrence, in order to obtain information about the chemical soil characteristics with native fruit presence. In general, only where the native fruits are present, they present weakly acid reaction and high organic matter, calcium, magnesium, phosphorus and potassium, as high CTC.